DOPE–oleic acid–Ca2+ as DNA condensing agent - Galliková, D.; Liskayová, G.; Búcsi, A.; Hubcík, L.; Martinez, Jorge; Uhríková, D. (2018)
Phospholipid-based non-viral carriers composed of neutral phospholipid dioleoylphosphatidylethanolamine (DOPE) and the binary mixture DOPE-oleic acid (OA) are examined as potential DNA delivery vectors. The process of DNA condensation in the presence of Ca2+ions has been monitored through changes in emmision intensity of fluorescent probe ethidium bromide. The decline in fluorescence intensity with increasing Ca2+concentration at two different time intervals was correlated with the binding capacity of complexes and possible release of DNA from the complex. The microstructure of DOPE-OA mixtures at different OA/DOPE molar ratios and that of DOPE-OA-DNA-Ca2+complexes were determined using synchrotron small angle X-ray diffraction (SAXD). We identified inverted hexagonal phase HIIas the dominant structure. OA affects the lattice parameter of HIIformed by DOPE. With the increasing OA/DOPE molar ratio, the lattice parameter decreases, which results in significantly lower fraction of DNA bound to the OA-enriched complexes.